Migration, youth, and agricultural productivity in Ethiopia - de Brauw, Alan (Agricultural and Applied Economics Association, 2015)
This paper explores the relationship between migration and agricultural productivity in Ethiopia. Given that there are fairly significant returns to either rural-urban or international migration for labor in Ethiopia, it could be that credit constraints hindering migration start-up are an unexplored constraint against migration. The paper primarily uses the Ethiopia Rural Household Survey panel and a migrant listing exercise completed after the 2009 survey round to explore whether past agricultural productivity (e.g. in 2004) explains later migration. Using standard regression techniques, it finds that among young migrants, there appears to be a positive, significant relationship between productivity and households sending out a migrant. This relationship holds even when proxies for credit are included in the model; the effect appears to, in fact, be stronger among households who are less endowed with land. However, the magnitude of this effect is small. The paper also considers feedback effects from migration to later agricultural productivity; this correlation is weaker suggesting that migration does not have negative productivity impacts. Brauw, Alan de